PTH-018 Predicting survival in palliative oesophageal stent insertion. (22nd June 2015) - Driver, R; Handforth, C; Kite, S; Radhakrishna, G; Hull, M; Everett, S
Abstract : Introduction: Self-expanding metal stents (SEMS) are an important treatment modality in palliation of malignant dysphagia, either alone or in addition to chemotherapy or radiotherapy. However, the optimal timing of stent insertion remains uncertain when considering prognosis in advanced malignancy. We present a large single centre experience of patients undergoing SEMS insertion for malignant dysphagia. The aim was to identify risk factors associated with overall and 30 day mortality post-oesophageal stenting. Method: All patients receiving an oesophageal stent for palliation of dysphagia in primary oesophageal malignancy between January 2009 and December 2013 in Leeds Teaching Hospitals NHS Trust were included. All devices used were Niti S double covered stents inserted by four experienced practitioners using a combined endoscopic and fluoroscopic procedure. Demographics, tumour site and stage, performance status, Charlson co-morbidity index, dysphagia score, previous oncological therapies and serum albumin and CRP in the week prior to stent insertion were retrieved from electronic patient records. Kaplan-Meier survival estimates and Cox proportional hazards regression were performed to identify risk factors predictive of mortality. Results: Among 259 patients (mean age 70.3 (range 32 to 99)), the median post-stent survival was 100 days (95% CI, 87 to 116). 51 patients (20%) died within 30 days of the stenting procedure and 10 patients (4%) died within 7 days. 35 patients (14%) required repeat stenting for tumour overgrowth, stricture or stent migration; the median time to re-stent was 137 days (95% CI, 99 to 175). Serum CRP > 50 was an independent predictor of 30 day mortality (hazard ratio [HR], 3.7; 95% CI, 1.7 to 8.0). Overall post-stent mortality was associated with CRP > 50 (HR, 2.3; 95% CI, 1.6 to 3.2) and albumin < 30 (HR, 1.9; 95% CI, 1.1 to 3.1). Conclusion: Our 30 day mortality of 20% is consistent with data published elsewhere (13 1 –25% 2 ), but this study identifies the association of elevated CRP with short-term mortality. This may reflect advanced disease or concurrent infection (such as aspiration pneumonia) and may be a useful guide to optimising timing of stent insertion. Disclosure of interest: None Declared. References: Homs MY, Steyerberg EW, Eijkenboom WM, et al . Single-dose brachytherapy versus metal stent placement for the palliation of dysphagia from oesophageal cancer: multicentre randomised trial. Lancet 2004;364(9444):1497–504 van Heel NC, Haringsma J, Boot H, et al . Comparison of 2 expandable stents for malignant esophageal disease: a randomized controlled trial. Gastrointestinal Endoscopy;76(1):52–8